Efficacy and safety of Ophiocordyceps sinensis in the treatment of Hashimoto's thyroiditis: a systematic review and meta-analysis - Maoying Wei; Wenxin Ma; Wenhua Zhang; Dan Yin; Yiting Tang; Weiyu Jia; Yijia Jiang; Churan Wang; Yanbing Gong (Frontiers Media S.A., 2023)
Objective: To evaluate the efficacy and safety of Ophiocordyceps sinensis (OS) preparations for the treatment of Hashimoto's thyroiditis (HT).Methods: We searched eight databases to collect randomized controlled trials (RCTs) of OS combined with a low-iodine diet or levothyroxine for HT. The search period was from inception to June 2023. Meta-analysis was performed using Revman 5.3 software after two evaluators independently screened the literature, extracted data, and evaluated the risk of bias of the included studies. The GRADE system was used to assess the certainty of evidence.Results: A total of 14 RCTs involving 1,014 patients with HT were included. Meta-analysis showed that OS preparations combined with a low-iodine diet were more effective in reducing thyroid peroxidase antibody (TPOAb) [SMD = −3.81, 95% CI (−5.07, −2.54), p < 0.00001] and thyroglobulin antibody (TgAb) [SMD = −4.73, 95% CI (−6.86, −2.61), p < 0.00001] compared to a low-iodine diet. Compared with levothyroxine treatment alone, OS preparations combined with levothyroxine further reduced TPOAb [SMD = −2.04, 95% CI (−2.82, −1.26), p < 0.00001], TgAb [SMD = −2.01, 95% CI (−2.68, −1.33), p < 0.00001], tumor necrosis factor alpha (TNF-α) [SMD = −3.40, 95% CI (−5.66, −1.14), p = 0.003], interleukin-2 (IL-2) [SMD = −2.31, 95% CI (−3.98, −0.65), p = 0.006], and interleukin-6 (IL-6) [MD = −4.16, 95% CI (−6.17, −2.15), p < 0.0001], and elevated free thyroxine (FT4) [SMD = 1.34, 95% CI (0.59, 2.08), p = 0.0004], but no significant effect on free triiodothyronine (FT3) [SMD = 0.83, 95% CI (−0.12, 1.78), p = 0.09] and thyroid stimulating hormone (TSH) [SMD = −0.80, 95% CI (−1.71, 0.11), p = 0.08]. In terms of safety, three studies reported adverse reactions in 10 patients in each of the experimental and control groups.Conclusion: OS preparations in combination with other treatments (low-iodine diet or levothyroxine) may decrease thyroid autoantibodies and inflammatory responses in patients with HT. In HT patients with hypothyroidism, the combination of the OS preparations with levothyroxine also improved FT4. However, the quality of the included studies was generally low. Moreover, the safety of OS preparations remains unclear. Therefore, more high-quality, multicenter, large-sample RCTs are needed in the future to validate the efficacy and safety of OS preparations.Systematic Review Registration:https://www.crd.york.ac.uk/prospero, identifier CRD42023432663